Essentials of Financial Management - Laws, Jason (Liverpool University Press, 2018)
Essentials of Financial Management is an Open Access e-textbook (paperback edition also available) suitable for students with limited knowledge of finance and financial markets. It answers the main questions of a corporate entity, such as how businesses finance their activities, how they select projects to invest in, the distribution of net cash flow and, of increasing importance, how businesses manage price risk relating to cost of goods sold or a decline in revenue. In providing invaluable guidance to finance, management and business students, Essentials of Financial Management employs two main philosophies: that finance is a real-life subject and that finance is a numerical subject, which is why this brilliant e-textbook contains real world examples as well as numerous Excel spreadsheet solutions for students to download and use.